Analisis Wacana Kritis Model Teun A. Van Dijk dalam Lirik Lagu “Politik Uang” Karya Iwan Fals - Saputri, Vioni; Fajrin, Rafika (LP2M, Institut Agama Islam Qamarul Huda, 2021)
The purpose of this research is to reveal messages in discourse. The research design used is descriptive qualitative research. The subject of the research is the lyrics of the song Politics of Money by Iwan Fals. The method used is the method of documentation and content review. Through this method, the data contained in the lyrics of the song Politics of Money by Iwan Fals is collected as data. Furthermore, the content study method is used to obtain data about discourse texts and which ones are included in the study of critical discourse analysis. Data analysis includes two things (1) data presentation and (2) data verification and inference. The lyrics of the song, entitled Money Politics, expresses the author's feelings about the sad state of government in Indonesia, especially during the election. Fraud and acts that harm the author conveyed. From the results of the study it was found that from (1) text analysis, there was a macro structure analysis, namely thematic, super structure analysis, namely the scheme of the lyrics of the Money Politics song, micro structure analysis, namely background, detail, and intent, presuppositions, nominalization, sentence form, coherence, pronouns, lexicon, and interactions and expressions. (2) There are four schemes for social cognition, namely the person, self, role, and event schemes in the lyrics of the song Politics of Money. (3) Social analysis is to explain the relationship of election discourse in the lyrics of the song Politics of Money. Tujuan penelitian untuk mengungkapan pesan dalam wacana. Rancangan penelitian yang digunakan adalah penelitian deskriptif kualitatif. Subjek penelitiannya adalah lirik lagu Politik Uang karya Iwan Fals. Metode yang digunakan ialah metode dokumentasi dan telaah isi. Melalui metode ini data-data yang termuat dalam lirik lagu Politik Uang karya Iwan Fals dikumpulkan sebagai data. Selanjutnya metode telaah isi digunakan untuk mendapatkan data tentang teks wacana dan mana saja yang termasuk dalam kajian analisis wacana kritis. Analisis data mencakup dua hal (1) penyajian data dan (2) verifikasi dan penyimpulan data. Lirik lagu yang berjudul Politik Uang ini mengungkapkan perasaan penulis akan mirisnya keadaan pemerintahan di Indonesia terlebih dalam berlangsungnya pemilu. Kecurangan dan tindak-tindak yang merugikan disampaikan penulis. Dari hasil penelitian ditemukan bahwa dari (1) analisis teks, terdapat analisis struktur makro yaitu tematik, analisis super struktur yaitu skema dari lirik lagu Politik Uang, analisis struktur mikro yaitu latar, detail, dan maksud, praanggapan, nominalisasi, bentuk kalimat, koherensi, kata ganti, leksikon, serta interaksi dan ekspresi. (2) Kognisi sosial terdapat empat skema yaitu skema person, diri, peran, dan peristiwa dalam lirik lagu Politik Uang. (3) Analisis Sosial ialah menjelaskan hubungan wacana pemilu dalam lirik lagu Politik Uang.